Evaluasi Pelaksanaan Supervisi Klinis dalam Peningkatan Standar Proses Dikalangan Guru-Guru Matematika di SMA Negeri 1 Pandawai - Mbelu Ranjawali, Ronexon; Iriani, Ade; Wasitohadi, Wasitohadi (Manajemen Pendidikan, 2019)
The aims of this study is to evaluate the implementation of clinical supervision in improving standard process for mathematics teachers in SMA Negeri 1 Pandawai. This study is an evaluation research. By using a discrepancy model. Data collections uses interviews, observation, and documentation. The subjects of the research is principal, vice principals and mathematics teachers. The results of this study stated that: 1) at the design stage,the principal has planned well about the implementation of clinical supervision, but in teacher teaching practices there are still gaps especially in the steps of learning (in preliminary activities, core activities, and closing activities); 2) at the installation stage, the teacher has done and paid attention to three aspects of learning, namely planning, implementation, and evaluation based on government regulations; 3) at the process stage, the school has made joint decisions, and has understood and carried out clinical supervision procedures. However, the follow-up aspects have not been carried out by schools to mathematics teachers according to the schedule, and the procedures have been set; 4) at the outcome stage, there are still differences between the results and the expected ones. It caused because the teacher has not doing innovated learning and evaluation at the end of each lesson.At the end of the material in each chapter, the teacher?s lack of ability to manage the class so that student learning interest decreases.